Developing Employee Counselling - Upton, Dave (Cranfield University, 1997)
The research focused on the counselling service provided by a major national N-1 organisation. The main aim was identification of managerial mechanisms that might be instituted to facilitate the development of workplace counsellors.It comprised of three main studies which utilised both quantitative and qualitative methods. Over a period of eight months,corresponding quantitative data were collected after each new counselling session from six hundred and ninety-four clients and forty-six counsellors.In addition, qualitative data in the form of case notes were obtained from the counsellors, forty-three of whom also completed Levenson's (1981) Locus of Control questionnaire. In the first study,quantitative questionnaire data from both clients and counsellors were analysed in order to investigate discrepancies between the two groups that might identify a means of focus for managing the service. Statistical exploration of sociodemographic features that might be implicated as potentially confounding variables in the assessment of counselling effectiveness and client satisfaction was also undertaken, and the proposition that non-respondents perceive less benefit from the service was indirectly explored. A dditionally,the relationship between some of the Rogerian core qualities and client perceptions of benefit was investigated. In the second study,qualitative data from counsellor notes were examined in order to establish the type of notes produced and to consider ways in which counsellors might be encouraged to focus on counselling process rather than content. As a result an instrument was developed which provides a tool to facilitate counsellor development within a professional supervisory re lationship, inside or outside of the organisational context. The third study was designed to investigate counsellors' own locus of control and their perceptions of their clients' primary loci. Objectives of the study included comparison of the two measures and exploration of relationships between locus of control and other issues of interest to the research such as client perception of benefit from counselling, perceived use of Rogerian core variables and results on the process measure. The findings of the studies and their implications for counsellor development are fully discussed and suggestions for future research are provided.